2021
DOI: 10.1186/s12905-021-01310-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cost analysis of cervical cancer screening programme based on molecular detection of HPV in Spain

Abstract: Background HPV cervical cancer screening (CCS) must use validated HPV tests based on the molecular detection of either viral mRNA (Aptima HPV Assay—AHPV) or DNA. AHPV has demonstrated the same cross-sectional and longitudinal sensitivity for the detection of HSIL/CIN2+ lesions but with greater specificity than HPV-DNA tests. The study aimed to estimate the total costs of a CCS with a primary HPV test based on the detection of mRNA compared to DNA in women aged 35–65 years for the National Healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This analysis is in line with the methodology of a previous study that compared the cost-effectiveness of high-risk HPV testing using a DNA-based assay and a mRNA-based assay under the US cervical cancer screening guidelines [8]. The same methodology was also used in recent studies in Europe, namely in the United Kingdom [25] and in Spain [26], where it was concluded that testing for HPV infection with mRNA-based assays generate less costs and consumes less health resources (i.e.,…”
Section: Discussionsupporting
confidence: 74%
“…This analysis is in line with the methodology of a previous study that compared the cost-effectiveness of high-risk HPV testing using a DNA-based assay and a mRNA-based assay under the US cervical cancer screening guidelines [8]. The same methodology was also used in recent studies in Europe, namely in the United Kingdom [25] and in Spain [26], where it was concluded that testing for HPV infection with mRNA-based assays generate less costs and consumes less health resources (i.e.,…”
Section: Discussionsupporting
confidence: 74%
“…All slides were annotated with regions of interest with a total of 576 annotations (mean, 6.12 [range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] annotations per case).…”
Section: Scanning and Digital Platformmentioning
confidence: 99%
“…2 In Europe, many countries have implemented HR HPV primary screening programs either regionally or nationally. [3][4][5][6][7][8] In the era of HR HPV primary screening, the number of cervical cytology slides has dramatically decreased, but there is a relative increase in atypical cytological findings at least in the first screening round. 6,7 Low-grade changes of the squamous epithelia include both atypical squamous cells of undetermined significance (ASC-US) and low-grade squamous intraepithelial lesion (LSIL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation